2019
DOI: 10.1002/aocs.12275
|View full text |Cite
|
Sign up to set email alerts
|

Lipid Vesicle Preparation Using W/O/W Multiple Emulsions Via Solvent Evaporation: The Effect of Emulsifiers on the Entrapment Yield of Hydrophilic Materials

Abstract: We studied the effects of emulsifiers on the entrapment yields of a hydrophilic material, calcein, in lipid vesicles formed using the multiple emulsion method. The primary emulsion (W 1 /O) was prepared via sonication while the secondary emulsification that produced the W 1 /O/W 2 multiple emulsions was achieved using the microchannel (MC) emulsification technique. The emulsifiers used in the continuous (W 2 ) phase were Tween ® 80, Pluronic ® F68, and bovine serum albumin (BSA). Lipid vesicles formed via solv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 35 publications
(44 reference statements)
3
2
0
Order By: Relevance
“…According to Kuroiwa et al [22], the use of 3.0 wt % (w/v) Tween ® 80 with a relative molecular weight of 1310 as an emulsifier in the external water phase resulted in an entrapment yield of as low as 20% for calcein. Previously, Ossai et al [23] suggested that the entrapment yield of calcein increased with a decrease in Tween 80 concentration, which conforms with our present study in which an appreciable entrapment of 40.12% for MH was obtained at low concentration (0.1 wt %) of Tween ® 80 as the external water phase emulsifier. The lower entrapment yields of the current work's formulation compared with that previously established by Ossai et al [23], specific to the entrapment of calcein, could be due to either efflux or leakage of the entrapped material from the internal aqueous phase to the continuous aqueous phase, which might have partially taken place as the solvent evaporation proceeded.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…According to Kuroiwa et al [22], the use of 3.0 wt % (w/v) Tween ® 80 with a relative molecular weight of 1310 as an emulsifier in the external water phase resulted in an entrapment yield of as low as 20% for calcein. Previously, Ossai et al [23] suggested that the entrapment yield of calcein increased with a decrease in Tween 80 concentration, which conforms with our present study in which an appreciable entrapment of 40.12% for MH was obtained at low concentration (0.1 wt %) of Tween ® 80 as the external water phase emulsifier. The lower entrapment yields of the current work's formulation compared with that previously established by Ossai et al [23], specific to the entrapment of calcein, could be due to either efflux or leakage of the entrapped material from the internal aqueous phase to the continuous aqueous phase, which might have partially taken place as the solvent evaporation proceeded.…”
Section: Discussionsupporting
confidence: 93%
“…Previously, Ossai et al [23] suggested that the entrapment yield of calcein increased with a decrease in Tween 80 concentration, which conforms with our present study in which an appreciable entrapment of 40.12% for MH was obtained at low concentration (0.1 wt %) of Tween ® 80 as the external water phase emulsifier. The lower entrapment yields of the current work's formulation compared with that previously established by Ossai et al [23], specific to the entrapment of calcein, could be due to either efflux or leakage of the entrapped material from the internal aqueous phase to the continuous aqueous phase, which might have partially taken place as the solvent evaporation proceeded. Specifically, the lower relative molecular weight of MH (165.6 g/mol) might be an explanation for this occurrence (of efflux or leakage of the entrapped material), compared with that of calcein (622.6 g/mol), of the current work.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Different kinds of emulsification devices can be used to form W 1 /O/W 2 emulsions, including high‐pressure valve homogenization (HPVH), microfluidization, sonication, high‐speed shearing and membrane homogenization 8‐10 . Often, a relatively high‐intensity method (such as HPVH, microfluidization and sonication) is used to form W 1 /O emulsions containing small water droplets dispersed in oil, then a relatively low‐intensity method (such as high‐speed shearing or membrane homogenization) is used to form the W 1 /O/W 2 emulsions.…”
Section: Introductionmentioning
confidence: 99%
“…Different kinds of emulsification devices can be used to form W 1 /O/W 2 emulsions, including high-pressure valve homogenization (HPVH), microfluidization, sonication, high-speed shearing and membrane homogenization. [8][9][10] Often, a relatively highintensity method (such as HPVH, microfluidization and sonication) is used to form W 1 /O emulsions containing small water droplets dispersed in oil, then a relatively low-intensity method (such as high-speed shearing or membrane homogenization) is used to form the W 1 /O/W 2 emulsions. However, in some cases it is also possible to use the same homogenizer but operated at different intensities, such as creating the W 1 /O emulsions using a high operating pressure, then creating the W 1 /O/W 2 emulsions using a lower operating pressure with the same HPVH.…”
Section: Introductionmentioning
confidence: 99%